Hubungan Kadar Awal D-Dimer Terhadap Mortalitas pada Pasien COVID-19 Di RSUP Dr. Sardjito - Alqustar, Adam; Kurniawaty, Juni; Widyastuti, Yunita (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
In severe COVID-19 infection, the immune response can be exaggerated andcause a systemic cytokine storm that triggers systemic inflammatory responsesyndrome (SIRS). Excessive systemic inflammatory response can lead to systemicendothelial injury (endotheliopathy) and a hypercoagulable state that increasesthe risk of systemic macrothrombosis and microthrombosis. D-dimers arereleased when plasmin, a fibrinolytic enzyme, breaks down fibrin and is areflection of the endovascular thrombosis process. Assessment of circulating Ddimer concentrations is a sensitive test for diagnosing thrombotic status(including pulmonary embolism and DIC) and predicting mortality event inpatient contracted with COVID- 19